A critical review of emotional abuse and sextortion among Ghanaian women on social media / Basiratu Lawal, Mokhtar Muhammad and Shazleen Mohamed - Lawal, Basiratu; Muhammad, Mokhtar; Mohamed, Shazleen (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
One of the greatest challenges in handling domestic abuse cases in Ghana is that abused women encounter opposition in reporting any form of abuse. This opposition is due to the inherent cultural norms which influence the support that any form of abuse in marriage is a private family affair that must be settled outside the criminal justice system. In spite of these challenges, most women continue to report incidents of domestic violence. This study provides a systematic review of abuse cases leading to sextortion and understanding of the main causes of Emotional Abuse and Sextortion among Ghanaian Women. Literature dated from January 1999 until January 2019 were identified by searching the appropriate keywords through international databases such as MEDLINE Web of Science, PubMed, Scopus, Cochrane and Google Scholar, Science direct. The interesting findings of this research shows that Social Media (via WhatsApp, Facebook, Instagram) is the cause of abuse that manipulate women’s feelings and emotions by maltreating them in an emotional way and eventually affect their well-being. Evidence suggests that social media is among the most important factors that contribute to cyberbullying of vulnerable women in Ghana. Future researcher should look into smart factory company(s) that can use robots to detect sensitive images/videos on any device via smart phones. to help make the work of the law enforcement and police officers easy. Future researcher can also add on the research weight to look into forwarding nude pictures, videos and any form of sensitive images to be punishable under law.